2020
DOI: 10.1097/qad.0000000000002484
|View full text |Cite
|
Sign up to set email alerts
|

Presence of asymptomatic cytomegalovirus and Epstein--Barr virus DNA in blood of persons with HIV starting antiretroviral therapy is associated with non-AIDS clinical events

Abstract: Background: Even with antiretroviral therapy (ART), persons with HIV (PWH) experience increased morbidity and mortality. Cytomegalovirus (CMV) and Epstein--Barr virus (EBV) co-infections likely exacerbate inflammatory-related diseases. Objective: To determine if presence of detectable CMV or EBV DNA in peripheral blood mononuclear cells (PBMC) is associated with non-AIDS events among PWH receiving modern ART. Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…It is conceivable that CRP does not adequately capture this brain-immune relationship, since the aforementioned studies reported associations between FA and inflammatory cytokines rather than CRP. Specific markers of viral infection such as CXCL10/IP-10 or macrophage activation such as sCD14 may also be more sensitive to HCMV reactivation than CRP [122]. Another possibility is that that the single time point at which CRP was measured did not always overlap with viral shedding since the two studies were not designed to enroll participants with an active HCMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that CRP does not adequately capture this brain-immune relationship, since the aforementioned studies reported associations between FA and inflammatory cytokines rather than CRP. Specific markers of viral infection such as CXCL10/IP-10 or macrophage activation such as sCD14 may also be more sensitive to HCMV reactivation than CRP [122]. Another possibility is that that the single time point at which CRP was measured did not always overlap with viral shedding since the two studies were not designed to enroll participants with an active HCMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,9,[25][26][27] Furthermore, our analyses may be restricted by the lack of information on several unmeasured confounders in UK CHIC known to modulate immune responses, including infection by cytomegalovirus and other human herpesvirus, tobacco, and alcohol use. [28][29][30][31][32] Finally, the small number of new AIDS events in the study means that our analyses may be underpowered to detect some associations.…”
Section: Cd41:cd81 T Cell Ratio and Aids Risk On Artmentioning
confidence: 99%
“…For instance, Kenyan children on ART exhibited a correlation between EBV primary infection and HIV viremia, which supports that EBV influences HIV reactivation [ 140 ]. Similarly, detectable EBV load at the initiation of ART or post-ART was associated with positive markers of inflammation, non-AIDS defined malignancies, and other PLWH morbidities, such as cardiovascular disease [ 141 ]. EBV load in the peripheral blood correlates with hypergammaglobulinemia and with the presence of LMP1-transcripts in cells, despite ART-suppressive HIV viremia and increased CD4 numbers [ 142 ].…”
Section: Hiv Steady B Cell Stimulation Creates a Lymphomagenesis Permissive Environmentmentioning
confidence: 99%